Double-parameter sensing of voltage and magnetic field based on photonic crystal fiber - Shi, Weihua; Mu, Rongqiu; Guo, Xiaochen; Jiang, Rushan; Shangguan, Mingyu; Li, Qing Feng; Zhang, Huiyi; Zhang, Ling; Wan, Hongdan (Frontiers in Physics, 2022)
In this paper, a new type of photonic crystal fiber (PCF) sensor is proposed for detecting the voltage and magnetic field simultaneously. In the PCF, an air hole of the cladding is coated with gold film and filled with the liquid crystal, thus the surface plasmon resonance (SPR) channel is formed to detect the voltage. While another air hole of the cladding is filled with magnetic fluids, the directional coupling channel is formed to detect the magnetic field. The SPR sensing channel and directional coupling channel are relatively independent. A finite element method (FEM) has been used for the optimization of the structure parameters, transmission characteristics of different modes, and analysis of the sensing characteristics. Numerical results reveal that the voltage sensitivity is 2.11 nm/V in the range of 5-35 V and the magnetic field sensitivity is 0.86 nm/Oe in the range of 90-210 Oe.